Hubungan Antara Religiusitas Dengan Kecenderungan Seks Pranikah Pada Remaja Di Pesantren Islam X, Asrama Katolik Y, dan Asrama Kristen Z - Alfie, Ahmad Ridwan Taufik; Sanjaya, Ersa Lanang (Universitas Ciputra Surabaya, 2019)
The purpose of this study is investigating the correlation between religiosity and intention to engage in premarital sex in adolescents at Islamic Boarding School X, Catholic Boarding School Y, and Christian Boarding School Z. The hypothesis of this study is H0, there is not correlation religiosity and tendency of sex before marriage in boarding school of religion, and H1, there is a negative correlation between religiosity and tendency of sex before marriage in boarding school of religion. The Samples were 152 students which is studying in boarding school of religion. This study used quantitative method with correlational design. Data were collected using religiosity scale that was been adopted from Aryati, and tendency of sex before marriage that was been adopted from Sanjaya, E L. The result showed that there is a negative correlation between religiosity and tendency of sex before marriage in boarding school of religion (r = -0,635, p = 0,000). That means the higher religiosity of the student, the lower the tendency to do sex before marriage in boarding school of religion and vice versa.